A balancing act: women players in a new semi-Professional team sport league. Issue 4 (4th July 2022) - Taylor, Tracy; Fujak, Hunter; Hanlon, Clare; O'Connor, Donna
ABSTRACT: Research question: Women commencing semi-professional careers in traditionally male team sports face unique opportunities and challenges. This study aimed to understand player's personal, organisational and societal barriers and supportive practices in their inaugural season as a semi-professional. Research methods: Players ( N =46) contracted for the 2019 National Rugby League Women's Premiership (Australia and New Zealand) completed an on-line questionnaire about the new league at the end of the first playing season. Additionally, players, coaches, and managers/executives ( N = 22) were interviewed about this newly constituted career pathway and the 'professionalisation' of the women's game. Results and findings: Data gathered were interrogated using an ecological-intersectional schema. Players were highly motivated intrinsically and strongly supported in their interpersonal environments. While the introduction of player payments was accompanied by increased expectations of the employing clubs; the level of remuneration was not viewed as sufficiently recompensing players for associated training, travel, playing and community commitments. Players with childcare responsibilities faced distinct barriers, with organisational policies yet to account for the distinct needs of this significant demographic cohort. Implications: In the first season adoption of existing, traditionally male-based, organisational norms and practices acted to legitimise the new women's competition, but also placed considerable stress on players. Most of the players had two or more employment commitments simultaneously yet had limited job security. Policies and practices with the greatest positive impact for the women players included: child-care provision, development of an inclusive team and club culture, and providing coaching, training and support specifically tailored to meet women's needs.